What is the effectiveness of community-based health promotion campaigns on chlamydia screening uptake in young people and what barriers and facilitators have been identified? A mixed-methods systematic review. (26th August 2021) - Pearce, Emma; Jolly, Kate; Harris, Isobel Marion; Adriano, Ada; Moore, David; Price, Malcolm; Ross, Jonathan
Abstract : Background: The UK National Chlamydia Screening Programme uses an opportunistic approach. Many programmes use campaigns to raise awareness of chlamydia screening in young people. This review aimed to assess the effectiveness of campaigns on uptake of chlamydia screening in young people. Methods: We conducted a mixed-methods systematic review of articles assessing the outcomes of community-based health-promotion campaigns to increase chlamydia screening in young people, their experiences of the campaigns and other facilitators and barriers to the conduct of the campaigns. We searched four databases for quantitative and qualitative studies with no language restrictions. Main results: From 10 329 records identified, 19 studies (20 articles) were included in the review: 14 quantitative, 2 qualitative and 3 mixed methods. All studies with quantitative outcomes were before-after study designs or interrupted time series. The prediction interval for relative change (RC) in test counts ranged from 0.95 to 1.56, with a summary pooled estimate of RC 1.22 (95% CI 1.14 to 1.30, 13 studies, I 2 =97%). For test positivity rate, 95% prediction interval was 0.59 to 1.48, with a summary pooled estimate of RC 0.93 (95% CI 0.81 to 1.07, 8 studies, I 2 =91.8%). Large variation in characteristics between studies precluded exploring outcomes by type of campaign components. Seven major qualitative themes to improve screening were identified: targeting of campaigns; quality of materials and message; language; anonymity; use of technology; relevance; and variety of testing options. Conclusions: Health promotion campaigns aiming to increase chlamydia testing in those aged 15–24 years may show some effectiveness in increasing overall numbers of tests, however numbers of positive tests do not follow the same trend. Qualitative findings indicate that campaigns require clear, relevant messaging that displays the full range of testing options and assures anonymity in order to be effective.